O assédio moral como elemento de visualização da violência simbólica : uma análise das sentenças trabalhistas da Comarca de Cuiabá/MT - Silva, Aline Rossiter Fonseca da (2020)
The present research project is inspired by the challenge of approaching Sociology and Law and aims to analyze the content of the decisions made by the judges of the Specialized Courts of Labor Courts of Cuiabá - MT, in the year 2017, seeking understand the phenomenon of symbolic violence in correlation with actions that deal with bullying. In summary, we believe that a notion of contemporary is broad and wide and diverse, being disseminated in societies, constituting itself as an excess power device (TAVARES DOS SANTOS, 2009). Violence, therefore, permeates moral harassment at work, becoming one of its modalities, which acts as a social practice. Labor moral harassment, according to Marie-France Hirigoyen (2003) can present itself in different ways, between words, writings, gestures and even in omissive behaviors, they act to dominate the other, reaching their dignity. Aware of this process of subjection of workers, due to their fragility, we resorted, especially to Pierre Bourdieu's concepts of symbolic violence and habitus, to answer the question at the end of the research: symbolic violence interferes in bullying practices in work relationships? Thus, we formulate the following hypothesis: because it is an invisible and imperceptible violence, it becomes the main resource for the aggressor to externalize and commit acts of moral harassment at work. As secondary objectives, we seek, based on the position of the Labor Justice, to identify the most frequent harassing practices, the professional branches with the highest incidence of this type of conduct, the gender of the affected agents and their position in the power scale of these relationships, relationships, in the end, a portrait of workplace bullying in the capital of Mato Grosso. The methodological attributes of the dissertation are: research with a qualitative approach to the problem, with an initial exploratory and later descriptive phase, with data collection done at the website of the Regional Labor Court of the 23rd region, with a content analysis as a technique applied for the approximation of the data. The interpretation of the collected material also had the technological support of the N VIVO.12 software. Our results confirm the influence of symbolic violence on acts of moral harassment at work, legitimizing them through the authoritarianism present in asymmetrical power relations that are ingrained in our bodies, structures and histories.